Andrographolide, an Anti-Inflammatory Multitarget Drug: All Roads Lead to Cellular Metabolism - Rafael Agustín Burgos; Pablo Alarcón; John Quiroga; Carolina Manosalva; Juan Hancke (Molecules, 2020)
Andrographolide is a labdane diterpene and the main active ingredient isolated from the herb Andrographis paniculata. Andrographolide possesses diverse biological effects including anti-inflammatory, antioxidant, and antineoplastic properties. Clinical studies have demonstrated that andrographolide could be useful in therapy for a wide range of diseases such as osteoarthritis, upper respiratory diseases, and multiple sclerosis. Several targets are described for andrographolide, including the interference of transcription factors NF-κB, AP-1, and HIF-1 and signaling pathways such as PI3K/Akt, MAPK, and JAK/STAT. In addition, an increase in the Nrf2 (nuclear factor erythroid 2–related factor 2) signaling pathway also supports its antioxidant and anti-inflammatory properties. However, this scenario could be more complex since recent evidence suggests that andrographolide targets can modulate glucose metabolism. The metabolic effect of andrographolide might be the key to explaining the diverse therapeutic effects described in preclinical and clinical studies. This review discusses some of the most recent evidence about the anti-inflammatory and metabolic effects of andrographolide.